Analysis Of Factors Related To The Stroke In Patients With Stroke In Ward C 1st Floor And 2nd Floor In The Rssn Bukittinggi 2016 - Wati, Nani Repita; Husna, Elfira (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
Stroke still become a health problem of society, due to the high incidence of morbidity, mortalities, and disability. Stroke attack estimated 25% was recovered from the first stroke in five years. Stroke occurrence because of risk factors an unhealthy lifestyle. The aim of this research was to determine to analyze risk factors (smoking and sports habits, diet and medical check-up obedience) related to the causes of stroke attack. The research of methods was observational analytic with a retrospective approach. The result of this research shows that smoking habits unrelated to stroke occurrence (p-value 1,000). Diet obedience unrelated to stroke occurrence (p-value 0,952). Sport habits unrelated to stroke occurrence (p-value 0,501). Medical check-up obedience was unrelated to stroke occurrence (p-value 0,069). In conclusion, there is not a relationship between smoking habits, diet obedience, sport habits, and medical check-up obedience by the stroke. It is advisable to the institutional hospital can give information to stroke patients the cause of incidence stroke not only one but many factors, and then how to control to avoid stroke attack and recurrent stroke attack.